Beyond craft an anti-handbook for creative writers - Westbrook, Steve 1973-; Ryan, James (Literary studies, 2020)
"Simultaneously a handbook and a critique of one, Beyond Craft combines an orientation to the field of creative writing with an insight into current scholarship surrounding creative writing pedagogy. A much-needed alternative to the traditional craft guide, this text pairs advice and exercises on composition with an illuminating commentary on the issues surrounding these very techniques. Teaching the craft whilst apprising students of the issues of craft pedagogy, this book allows them to gain an awareness of how current pedagogy comes at the expense of larger and increasingly relevant cultural concerns. Westbrook and Ryan bring emerging writers into the larger conversations that define the field, inviting them to: - Contextualize their own writing practices and educational experiences in relation to the history of creative writing as an academic discipline. - Determine how New Critical lore and Romantic mythology may affect-even distort-their understanding of literary production. - Critically examine their notions of authorship, collaboration, and invention in relation to contemporary literary and rhetorical theory. - Understand and evaluate the economic, social, political, and professional challenges facing creative writers today. - Analyze the contemporary literary marketplace not only to identify potential publication contexts but also to understand how issues of diversity and bias affect writing communities. - Reflect on how increasingly rapid technological developments may affect their own writing and the future of literature. Earnestly self-aware throughout, Beyond Craft both inducts new writers into the field of creative writing and infuses them with an understanding of the wider dialogue surrounding their craft."